Eksplorasi Potensi Tumbuhan Berkhasiat Obat Diabetes Mellitus Pada Suku Dayak Bakumpai Barito Selatan Sebagai Penyusun Atlas Tanaman Berkhasiat Obat - Ilham Muamar; Nanik Lestariningsih; Ridha Nirmalasari (Lontara Journal of Health Science and Technology, 2021)
The Bakumpai Dayak tribe is very close to their ancestral culture, including in their efforts to maintain their health and self-medication, which still chooses to use traditional methods such as gathering various plants taken from forests or gardens. This study aims to obtain information about the types of plants used, parts of plant organs used and to find out how to use medicinal plants to treat Diabetes Mellitus according to the customs of the Bakumpai Dayak Tribe, Dusun Selatan District, Baru Village. After conducting the research, there were 10 types of medicinal plants for the efficacy of Diabetes mellitus according to the Bakumpai Dayak tribe. The plants that are often used are Earth Pegs, Ulin Trees, Sandalwood Trees, Pare, Sapat Trees, Muhur, Noni, Bidders and Halaban Wood. The most widely used parts of the plant are the roots and leaves. Utilization of medicinal plants by the Bakumpai Dayak tribe by making pills, soaking, boiling, watering or washing, smearing or affixing them. How to use most medicinal plants by boiling and soaking.